2022
DOI: 10.1101/2022.02.28.482415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acentrosomal spindles assemble from branching microtubule nucleation near chromosomes

Abstract: Microtubules are generated at centrosomes, chromosomes, and within spindles during cell division. Whereas microtubule nucleation at the centrosome is well characterized, much remains unknown about where, when, and how microtubules are nucleated at chromosomes. To address these questions, we reconstituted microtubule nucleation from purified chromosomes in meiotic Xenopus egg extract and found that chromosomes alone can form spindles. We visualized microtubule nucleation at chromosomes using total internal refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…TPX2 facilitates branching MT nucleation, whereby one MT is nucleated from a pre-existing one, enabling amplification of MTs throughout the spindle (Petry and Vale, 2015; Travis et al, 2022b). In fact, branching provides a majority of MTs in centrosomal spindles (David et al, 2019) and is the main source of MTs in acentrosomal spindles including Xenopus laevis (Decker et al, 2018; Gouveia, 2022). Recent work showed that TPX2 forms a condensed phase that concentrates numerous branching factors at spindle MTs, as well as unpolymerized tubulin that can be used to build new MTs (King and Petry, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…TPX2 facilitates branching MT nucleation, whereby one MT is nucleated from a pre-existing one, enabling amplification of MTs throughout the spindle (Petry and Vale, 2015; Travis et al, 2022b). In fact, branching provides a majority of MTs in centrosomal spindles (David et al, 2019) and is the main source of MTs in acentrosomal spindles including Xenopus laevis (Decker et al, 2018; Gouveia, 2022). Recent work showed that TPX2 forms a condensed phase that concentrates numerous branching factors at spindle MTs, as well as unpolymerized tubulin that can be used to build new MTs (King and Petry, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…TPX2 facilitates branching MT nucleation, whereby one MT is nucleated from a pre-existing one, enabling amplification of MTs throughout the spindle ( 24 , 25 ). In fact, branching provides a majority of MTs in centrosomal spindles ( 26 ) and is the main source of MTs in acentrosomal spindles including Xenopus laevis ( 27 , 28 ). Recent work showed that TPX2 forms a condensed phase that concentrates numerous branching factors at spindle MTs as well as unpolymerized tubulin that can be used to build new MTs ( 29 ).…”
mentioning
confidence: 99%
“…In large vertebrate spindles, branching MT nucleation forms most spindle MTs [2][3][4][5] . In this process, new MTs nucleate at a shallow angle on the side of pre-existing MTs, resulting in exponential self-amplification 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Both the augmin complex and TPX2 are spindle assembly factors (SAF), meaning that their binding to MTs is inhibited by binding of importins and released by RanGTP 13,14 . Given that RanGTP is present in a gradient centered around chromatin, branching MT nucleation is spatially regulated to promote nucleation near chromosomes 5,15,16 .…”
Section: Introductionmentioning
confidence: 99%